Artikel Pergeseran Bahasa pada Komunikasi Bilingual pada Mahasiswa EFL di Universitas Muhammadiyah Bone: Penelitian - Julita Aishah; Nurul Wisma Syarif; Putri Awalia; Satriani Satriani; Nurkhumaedah Nurkhumaedah; Asmaul Husna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the phenomenon of language shift in the communication of bilingual students in the English Language Education Department, Muhammadiyah University of Bone. Language shift is reviewed from its form, social factors, and strategic function in academic and non-academic interactions. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and recordings of natural conversations. The results show that language shift occurs in the form of code-switching and code-mixing which are influenced by the context of the situation, the interlocutor, the topic of conversation, and cultural identity. Language shift functions as a communication strategy to build solidarity, facilitate understanding, and affirm multilingual identity. The implications of this study encourage a translanguaging approach in language learning to optimize students' bilingual competence.